If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -8y + 2)(3x + -2c + 100) = 0 Reorder the terms: (2 + X + -8y)(3x + -2c + 100) = 0 Reorder the terms: (2 + X + -8y)(100 + -2c + 3x) = 0 Multiply (2 + X + -8y) * (100 + -2c + 3x) (2(100 + -2c + 3x) + X(100 + -2c + 3x) + -8y * (100 + -2c + 3x)) = 0 ((100 * 2 + -2c * 2 + 3x * 2) + X(100 + -2c + 3x) + -8y * (100 + -2c + 3x)) = 0 ((200 + -4c + 6x) + X(100 + -2c + 3x) + -8y * (100 + -2c + 3x)) = 0 (200 + -4c + 6x + (100 * X + -2c * X + 3x * X) + -8y * (100 + -2c + 3x)) = 0 (200 + -4c + 6x + (100X + -2cX + 3xX) + -8y * (100 + -2c + 3x)) = 0 (200 + -4c + 6x + 100X + -2cX + 3xX + (100 * -8y + -2c * -8y + 3x * -8y)) = 0 Reorder the terms: (200 + -4c + 6x + 100X + -2cX + 3xX + (16cy + -24xy + -800y)) = 0 (200 + -4c + 6x + 100X + -2cX + 3xX + (16cy + -24xy + -800y)) = 0 Reorder the terms: (200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y) = 0 (200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y) = 0 Solving 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-200' to each side of the equation. 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -200 + -800y = 0 + -200 Reorder the terms: 200 + -200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + -200 Combine like terms: 200 + -200 = 0 0 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + -200 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + -200 Combine like terms: 0 + -200 = -200 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -200 Add '4c' to each side of the equation. 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + 4c + -800y = -200 + 4c Reorder the terms: 100X + -4c + 4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -200 + 4c Combine like terms: -4c + 4c = 0 100X + 0 + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -200 + 4c 100X + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -200 + 4c Add '-16cy' to each side of the equation. 100X + -2cX + 16cy + 6x + 3xX + -24xy + -16cy + -800y = -200 + 4c + -16cy Reorder the terms: 100X + -2cX + 16cy + -16cy + 6x + 3xX + -24xy + -800y = -200 + 4c + -16cy Combine like terms: 16cy + -16cy = 0 100X + -2cX + 0 + 6x + 3xX + -24xy + -800y = -200 + 4c + -16cy 100X + -2cX + 6x + 3xX + -24xy + -800y = -200 + 4c + -16cy Add '-6x' to each side of the equation. 100X + -2cX + 6x + 3xX + -24xy + -6x + -800y = -200 + 4c + -16cy + -6x Reorder the terms: 100X + -2cX + 6x + -6x + 3xX + -24xy + -800y = -200 + 4c + -16cy + -6x Combine like terms: 6x + -6x = 0 100X + -2cX + 0 + 3xX + -24xy + -800y = -200 + 4c + -16cy + -6x 100X + -2cX + 3xX + -24xy + -800y = -200 + 4c + -16cy + -6x Add '24xy' to each side of the equation. 100X + -2cX + 3xX + -24xy + 24xy + -800y = -200 + 4c + -16cy + -6x + 24xy Combine like terms: -24xy + 24xy = 0 100X + -2cX + 3xX + 0 + -800y = -200 + 4c + -16cy + -6x + 24xy 100X + -2cX + 3xX + -800y = -200 + 4c + -16cy + -6x + 24xy Add '800y' to each side of the equation. 100X + -2cX + 3xX + -800y + 800y = -200 + 4c + -16cy + -6x + 24xy + 800y Combine like terms: -800y + 800y = 0 100X + -2cX + 3xX + 0 = -200 + 4c + -16cy + -6x + 24xy + 800y 100X + -2cX + 3xX = -200 + 4c + -16cy + -6x + 24xy + 800y Reorder the terms: 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -200 + 4c + -16cy + -6x + 24xy + 800y + 200 + -4c + 16cy + 6x + -24xy + -800y Reorder the terms: 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -200 + 200 + 4c + -4c + -16cy + 16cy + -6x + 6x + 24xy + -24xy + 800y + -800y Combine like terms: -200 + 200 = 0 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + 4c + -4c + -16cy + 16cy + -6x + 6x + 24xy + -24xy + 800y + -800y 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 4c + -4c + -16cy + 16cy + -6x + 6x + 24xy + -24xy + 800y + -800y Combine like terms: 4c + -4c = 0 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + -16cy + 16cy + -6x + 6x + 24xy + -24xy + 800y + -800y 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -16cy + 16cy + -6x + 6x + 24xy + -24xy + 800y + -800y Combine like terms: -16cy + 16cy = 0 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + -6x + 6x + 24xy + -24xy + 800y + -800y 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = -6x + 6x + 24xy + -24xy + 800y + -800y Combine like terms: -6x + 6x = 0 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + 24xy + -24xy + 800y + -800y 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 24xy + -24xy + 800y + -800y Combine like terms: 24xy + -24xy = 0 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 + 800y + -800y 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 800y + -800y Combine like terms: 800y + -800y = 0 200 + 100X + -4c + -2cX + 16cy + 6x + 3xX + -24xy + -800y = 0 The solution to this equation could not be determined.
| -25+(-16)= | | 2(7x+1)=86 | | 76(8686868686868686868686886866888+8)=7 | | 25/60=c/12 | | 7(-2x-3)=-7 | | x(16-x^2)^1/2 | | -10+v-17v=4 | | 24-2x=24 | | -5(-2+x)=25 | | (.5x+5)+[.5(.5x+5)+5]+.75[.5(.5x+5)+5]+5=0 | | b/45=8/9 | | 35=10+4t | | 2y=-19/33 | | a/32=9/16 | | 30=0.75x | | 3(4x-5)+2=4x-11 | | x^2-4x+120=180 | | X/515 | | 6w-11w=20 | | 7x-10=-70+2x | | -15+x-9-6=12x-8 | | 5(l-4)=60 | | -25w=q | | 6z^3-6z=0 | | 3(x-3)+3x=4x+3 | | 6+x=-4x+51 | | 47+6k=3k-2 | | 5/6x=x/8-1 | | 3(2)-11=2(2-2)-5 | | 16=3(2b-4)-2b | | -3(2x+4)+1=-11-6x | | 2(4-3x)=82-2x |